Dampak Kinerja Keuangan dan Pengungkapan Corporate Social Responsibility (CSR) terhadap Nilai Perusahaan - Prapanca, Detak (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2019)
The development of a company will illustrate the increasing asset of a company that will describe the value of a company. Company value can be reflected from financial performance (EPS, ROA and NPM) as well as corporate social responsibility (CSR) disclosure. In this research firm value is analyzed with financial performance data and corporate CSR in 5th interval from year 2011 to 2015. Based on research that has been done show that financial performance proxy with ratio of EPS, ROA and NPM partially only NPM which have significant influence, where The company's value will increase 2,207 if the company's net income is generated high. In addition, corporate value is also proxied with the disclosure of social responsibility (CSR), in this study CSR does not significantly influence. Corporate performance and social responsibility disclosure simultaneously based on the research that has been done have an ef ect on simultaneously and significantly. This is indicated by the value of testing the value of F - Calculate is greater than the value of F - Table. The test results obtained value F - count 3.079, the value when compared with the value of t - table has a larger value, for t - table produced with df = 4 and N = 54 of 2.54. This indicates that financial performance simultaneously / simultaneously af ect the value of the company. And based on the result of testing the significance value of 0,024 <0,05, this result indicate that financial performance and disclosure of social responsibility significantly influence company value.